1630. Antibiotics Prescribed for Infection Prophylaxis Prior to Dental Procedures Are Frequently Unnecessary in the United States. (26th November 2018) - Suda, Kj; Adimadhyam, Sruthi; Calip, Greg; Rowan, Susan; Gross, Alan E; Perez, Rose; Hershow, Ronald; McGregor, Jessina C; Evans, Charlesnika
Abstract: Background: Antibiotics are recommended prior to certain dental procedures ("antibiotic prophylaxis") in patients with select comorbidities to prevent serious distant site infections. Our objective was to assess the appropriateness of antibiotic prophylaxis by dentists using Truven, a national integrated medical, dental, and prescription (Rx) claims database of 350 commercial plans. Methods: Cross-sectional study of 8.7 million adult dental visits in 2015. Antibiotic prophylaxis was defined as Rx with <3 days supply dispensed within 7 days before a dental visit. Medical diagnoses were evaluated in medical/hospital claims from 2009 to 2015. Patients with hospitalizations and infection diagnoses 14 days prior to the Rx date were excluded. Appropriate antibiotic prophylaxis was defined as a dental visit with a procedure that manipulated the gingiva/tooth periapex in patients with an appropriate cardiac diagnosis. Chi Square and logistic regression were applied. Results: In 2015, 30, 726 antibiotics were prescribed for dental infection prophylaxis for 21, 986 patients (mean age=58.6 + 15.0 years; 55.9% female). Amoxicillin (68.5%) and clindamycin (14.7%) were most common. 29, 879 dental visits were associated with 69, 639 dental codes ([CDTs]; range 1–14 CDTs/visit). Most dental visits were diagnostic (65.9% of visits with >1 diagnostic CDT), preventative (53.0%), and restorative (11.2%). 98.4% of dental visits had an appropriate CDT for antibiotic prophylaxis. Comorbidities include orthopedic implants (45.4%) and cardiac diagnoses at the highest risk of infective endocarditis (22.2%). Per guidelines, 78.0% of dental visits with antibiotic prophylaxis were inappropriate. Amoxicillin was more likely to be inappropriate than other agents (OR=1.65; 95% CI: 1.55–1.76). Orthopedic implants (OR=3.35; 95% CI: 3.14–3.56), tooth implant procedures (OR=3.30; 95% CI: 2.48–4.39), females (OR=1.35; 95% CI: 1.27–1.43) and the western US (OR=1.22; 95% CI: 1.09–1.36) were associated with inappropriate prescribing. Conclusion: Antibiotic prophylaxis is prescribed for indicated dental procedures, but is not appropriately limited to patients with cardiac diagnoses per guidelines. Implementing antimicrobial stewardship efforts in dental practices may be an opportunity to improve antibiotic prescribing for infection prophylaxis. Disclosures: J. C. McGregor, Merck: Grant Investigator, Research grant.